Odpowiedź:
zad. 1.
a) b –28
b) g : a
c) 3(z + x)
d) (c – d) : 2
e) w : 8
f) (m · z)²
zad. 2.
a) 2a + 6 + 8a + 3 = 10a + 9
b) 3c – x + 4x + 8c – 2 = 11c + 3x – 2
c) 12bc – 2b + 5bc + 9 = 17bc – 2b + 9
zad. 3.
a) 4x + 3y – xy = 4 · 4 + 3 · 10 – 4 · 10 = 16 + 30 – 40 = 6
b) 3(x + y) + y³ = 3x + 3y + 10³ = 3 · 4 + 3 · 10 + 10³ =
= 3 · 4 + 3 · 10 + 1000 = 12 + 30 + 1000 = 1042
zad. 4.
a) 2a – 4 = 10
2a = 10 + 4
2a = 14 | : 2
a = 7
b) 8z + 5 = 38
8z = 38 – 5
8z = 33 | : 8
z = 4,125
zad. 5.
6(3x – 7) = 120
18x – 42 = 120
18x = 120 + 42
18x = 162 | : 18
x = 9
spr.
6(3x – 7) = 18x – 42 = 18 · 9 – 42 = 162 – 42 = 120
zad. 6.
a) 2d zł + 3b zł
b) 2 · ½b zł + 3b zł = b zł + 3b zł
c) 3 · ½b zł + 2b zł + (b zł + d zł) =
= 1,5b zł + 2b zł + (b zł + d zł)
zad. 7.
x + x + 25 – 16 = 60
2x + 9 = 60
2x = 60 – 9
2x = 51 | : 2
x = 25,5
zad. 8.
2x + 2 · 15 = 86
2x + 30 = 86
2x = 86 – 30
2x = 56 | : 2
x = 28 cm